Detection of integrons and Staphylococcal Cassette Chromosome (SCCmec) types in Staphylococcus aureus isolated from burn and non-burn patients - Ebrahimzadeh Namvar, Amirmorteza; Khodaei, Farzaneh; Bijari, Aslan; Rastegar Lari, Abdolaziz (International Journal of Health Sciences, 2015)
Background: Methicillin Resistant Staphylococcus aureus (MRSA) strains have been recognized as an important reason of infections in health care units. Integrons role in antibiotic resistance box gene transfer has been well recognized which are found in Gram positive bacteria. Objective: The aim of this study was analyzed of SCCmec typing and determine of integron classes in burn and non-burn specimens. Methodology: A total of 110 S. aureus strains were isolated from burn and non-burn patients. Antimicrobial susceptibility testing, detection of mecA gene, various SCCmec types and integrons classes were analyzed. Results: In antimicrobial susceptibility test in burn patients, resistant to both gentamicin and oxacilin and in non-burn patients resistance to oxacilin and cefepime showed the highest ratio In PCR molecular test (80%) and (52.7%) of strains harbored the mecA gene. Therefore five different SCCmec types were recognized among our studied strains. Subsequently, integron class I was evaluated as (94.5%) in burn and (12.7%) in non-burn isolates by the multiplex PCR method. Conclusion: Albeit MRSA strains have the hospital reservoir so may cause serious treats for hospitalized and non-hospitalized patients, hence clinical decision for prevention and treatment may develop due to, mecA gene, SCCmec elements and integrons detection in health care units. Â